Consumer switching intentions for telecoms services: evidence from Ireland. Issue 5 (May 2018) - Lunn, Peter D.; Lyons, Sean
Abstract: Despite long-standing market liberalisation and efforts to reduce switching costs, many consumers have never switched telecoms provider. This paper investigates how consumer and service characteristics relate to switching intentions, using a sample of fixed-line broadband, mobile telephony and landline telephony customers from a 2015 survey conducted by ComReg, Ireland's National Regulatory Authority. We add to previous work by examining a rich array of personal and service characteristics while controlling for both bill shock and expected gains from switching. We find that long-standing subscribers who have never switched are exceptionally resistant to switching. Bill shock is strongly associated with intention to switch, especially among those more inclined to switch. A similar effect arises for expected gains, especially gains over 20%. These results are consistent with both a preference for fair treatment and with behavioural barriers to switching that require large gains to overcome. The effects of bundling and of the few socioeconomic, supplier or application use characteristics that are statistically significant are smaller and not consistent across markets. This implies that willingness to switch is not simply a characteristic of certain social groups, but is more complex and context dependent.